Pengaruh Aroma Terapi Jahe Terhadap Keluhan Mual Muntah Pada Pasien Kanker Payudara Yang menjalani Kemoterapi Di Ruang Bima RSUD Sanjiwani Gianyar - I Nyoman Rimawan (ITKES Wiyata Husada Samarinda, 2021)
Nausea and vomiting are the most commonly complained effects of chemotherapy for cancer patients. The management of nausea and vomiting can inhibit the subsequent chemotherapy process, reduce the cure rate of cancer cases, and cause severe anticipatory type nausea and vomiting. Efforts to overcome complaints of nausea, vomiting through pharmacological therapy and can also be through non-pharmacological therapy, one of which is ginger aromatherapy. This study aimed at determine the effect of ginger aromatherapy towards nausea and vomiting complaints in breast cancer patients undergoing chemotherapy in Bima Room Sanjiwani Regional Hospital, Gianyar. The research method used is quantitative research with Pre-Experimental One-Group Pretest-Postest Design. The research sample consisted of 18 breast cancer patients who undergo chemotherapy with a purposive sampling technique. Data was collected with Rhode Index Nausea Vomiting Retcing and analyzed by the Wilcoxon Signed Rank Test statistic test. The results of the study were obtained from 18 respondents complaints of nausea and vomiting before being given the treatment, most of them were moderate, as many as 16 people (88.9%), while after treatment most of them were mild, as many as 14 people (77.8%). Statistical test results showed that there was an effect of ginger aromatherapy on complaints of nausea and vomiting in breast cancer patients undergoing chemotherapy in Bima Room Sanjiwani Regional Hospital, Gianyar (p value = 0.001; α = 0.05). Suggestions to the hospital management to make SOP for non-pharmacological therapy in dealing with complaints of nausea, vomiting, chemotherapy patients. Keywords : Breast Cancer, Chemotherapy, Vomiting Nausea; Ginger Aromatherapy